Development of a mathematics e-module using Polypad to improve fractional concept comprehension - Ahmad Naufal; Kowiyah Kowiyah (Curricula: Journal of Curriculum Development, 2025)
Understanding math concepts, especially on fraction material, is often a difficulty for students. This problem is exacerbated by the limitations of available learning resources and the underutilization of technology in schools, which results in low student interest and learning outcomes. The purpose of this study was to develop and evaluate the feasibility and effectiveness of Polypad-assisted math e-modules in improving understanding of the concept of fractional numbers. This research uses the Research and Development (RnD) method with the ADDIE model. The feasibility of the product is measured through validation from material, media, language, and teacher experts, while the effectiveness is measured through tests. The validation results indicate that the e-module is highly feasible to use. The effectiveness test demonstrated a significant increase in concept understanding, as evidenced by a rise in the average post-test score from 54.83 to 90.50, with an N-Gain score of 0.80, indicating a high category. Thus, this Polypad-assisted e-module proved to be feasible and effective as an alternative learning media that helps students understand the concept of fractions more concretely and visually.   Abstrak Pemahaman konsep Matematika, khususnya pada materi pecahan, seringkali menjadi kesulitan bagi peserta didik. Masalah ini diperparah oleh keterbatasan sumber belajar yang menarik dan minimnya pemanfaatan teknologi di sekolah, yang berakibat pada rendahnya minat dan hasil belajar peserta didik. Tujuan penelitian ini untuk mengembangkan serta mengetahui kelayakan dan efektivitas e-modul Matematika berbantuan Polypad untuk meningkatkan pemahaman konsep bilangan pecahan. Penelitian ini menggunakan metode Penelitian dan Pengembangan (RnD) dengan model ADDIE. Kelayakan produk diukur melalui validasi dari ahli materi, media, bahasa, dan guru, sedangkan efektivitasnya diukur melalui tes. Hasil validasi menunjukkan e-modul sangat layak digunakan. Uji efektivitas menunjukkan peningkatan pemahaman konsep yang signifikan, dibuktikan dengan peningkatan nilai rata-rata post-test menjadi 90,50 dari pre-test 54,83, dengan skor N-Gain sebesar 0,80 dalam kategori tinggi. Dengan demikian, e-modul berbantuan Polypad ini terbukti layak dan efektif sebagai media pembelajaran alternatif yang membantu peserta didik memahami konsep pecahan secara lebih konkret dan visual. Kata Kunci: bilangan pecahan; e-modul; pemahaman konsep; Polypad